Conceptual development of an augmented reality application for vehicle inspection in Kuwait - Alostad, Eisa A E B (2019)
Automotive inspection is the process of servicing or replacing vehicle components and is very crucial process to ensure that the safety, reliability, drivability, comfort and longevity of vehicles are well maintained. It is very complicated and difficult to teach new workers to carry out inspection task of vehicles, without close instruction and guidance. Many printed instruction manuals which include hundreds of diagrams were difficult and time consuming to follow and interpret. One of the main problem in Ministry of the Interior General Directorate of Traffic, Kuwait is there is no Standard Operating Procedure (SOP) for used vehicle in Kuwait. The procedure they used for used vehicle inspection depends on the insurance companies’ checklist: Ain Takaful Insurance, Aman Takaful Insurance and Kuwait International Takaful Insurance. The Ministry of the Interior General Directorate of Traffic Kuwait only issued an inspection checklist for newly registered vehicle. The aim of this research is to develop a standard operating procedure for under hood area for used vehicle inspection in Kuwait as the procedure for used vehicle inspection depends on the insurance company checklists. Furthermore, this research aim is to develop an Augmented Reality (AR) application, to evaluate the effectiveness of AR technology in assisting the task of used vehicle inspection training for the automotive industry. After the main problem in inspection stages have been identified, an AR application was developed using a 3D modeling software, animation software and Unity platform software for this inspection stage. The comparison between two different types of medium which are AR-based instruction and paper-based instruction were carried out. Tracker positioning and orientations were also investigated in order to obtain the best tracking identification. The overall research had taken place at the Ministry of the Interior General Directorate of Traffic Department of Technical Inspection, Kuwait, in order to analyses the effectiveness of implementing AR in automotive inspection compared to the traditional method of manual sheets‘ inspection. The participants were divided into two groups; Experimental group and expert group. The display of 2D instruction and rendered 3D model provide an interactive user interface as subject can guide themselves by touching the ‘next’ or ‘previous’ button on the screen. On the other hand, for manual paper based instruction, all the details of the maintenance procedure was written in a proper table format. Experiments to evaluate the effectiveness and acceptance level of AR application in inspection were compared to normal automotive inspection. Based on an overall evaluation, it was found that the developed application does offer benefits in inspection completion time. Results for a mean task completion time from the AR application validation shows that inspection using the AR application is better performed with a 10.72% time reduction compared to the conventional paper manual. It was also found that horizontal tracker placement has attained better measurement accuracy with 20.16% improvement compared to a vertical placement. Meanwhile trackers orientation does not have any significant role in the information feedback time. This work has successfully developed AR application which offers benefits in automotive inspection. Therefore, it was proven that the alternative learning and training method using Augment Application was the most preferred method based on the responses from both control groups.